Improved Ablation Efficiency in PVI Guided by Contact Force and Local Impedance: Chronic Canine Model - Gutbrod, Sarah R.; Shuros, Allan; Koya, Vijay; Alexander-Curtis, Michelle; Lehn, Lauren; Miklos, Kimberly; Mounsey, John Paul; Meyers, Jason D. (Frontiers in Physiology, 2022)
Background The purpose of this study was to assess the effect local impedance (LI) has on an ablation workflow when combined with a contact force (CF) ablation catheter. Methods Left pulmonary vein isolation was performed in an in vivo canine model (N= 8) using a nominal (30W) or an elevated (50W) power strategy with a CF catheter. The catheter was enabled to measure LI prior to and during ablation. LI was visible for only one of the vein isolations. Results Chronic block was achieved in all animals when assessed 30 +/-5 days post ablation procedure with a median LI drop during RF ranging from 23.0 – 34.0Ω. In both power cohorts, the median radiofrequency (RF) duration decreased if LI was visible to the operator (30W only CF: 17.0s; 30W CF + LI: 14.0s, p=0.009; 50W only CF: 6.0s; 50W CF + LI: 4.0s, p=0.019). An inverse relationship between the LI prior to RF delivery and the RF duration required to achieve an effective lesion was observed. There was no correlation between the magnitude of the applied force and the drop in LI, once at least 5g was achieved. Conclusiond An elevated power strategy with the context of CF and LI led to the most efficient titration of successful RF energy delivery. The combination of feedback allows for customization of the ablation strategy based on local tissue variation rather than a uniform approach that could potentially lead to overtreatment. Higher LI drops were more readily achievable when an elevated power strategy was utilized, especially in conditions where the catheter was coupled against tissue with low resistivity. Clinical study is warranted to determine if there is an additive safety benefit to visualizing the dynamics of the tisCathetersue response to RF energy with LI when an elevated power strategy is used.